The mechanical and biochemical effects of pentoxifylline on the perfused rat heart - Vittone, Leticia Beatriz (1980)
Perfusion of the isolated rat heart at constant heart rate and coronary flow with the inhibitor of cyclic nucleotide phosphodiesterase, pentoxifylline (10(-4) moles/l), produced no significant effect on the maximum rate and the peak of contraction, but increased the maximum rate of relaxation. cAMP level and cAMP-dependent protein kinase activity were increased in the absence of changes in cGMP. The results were identical in hearts of reserpinized rats.